Resource-based view and Service-dominant logic: Similarities, differences and further research - Cristina Mele; Valentina Della Corte (jbm - Journal of Business Market Management, 2013)
In this paper the authors apply a meta-theory analysis to compare two theoretical approaches: the resource-based view (RBV) and service-dominant logic (S-D logic). The comparison is based on three aspects: 1. a general profile; 2. the role of resources; 3. the conceptualisation of value. The authors give insights to a deeper understanding of the two approaches and their possible interdependencies without reducing multiplicity and complexity. The analysis ends with suggestions for further research.
urn:nbn:de:0114-jbm-v6i4.666
Keywords: 650; Resources; Activities; Actors; Value